High polarity extracts obtained from Ilex guayusa Loes. leaves, exhibit antioxidant capacity - RODRIGUEZ AGUIRRE, OSCAR EDUARDO; Castañeda Villate, Jenny Carolina; Hernández Roa, Mayerly Johanna; Cárdenas Tavera, Camila Florenza; Pombo Ospina, Luis Miguel; Borrego Muñoz, Paola (Vitae, 2022)
Background: Ilex guayusa Loes. belongs to the family Aquifoliaceae. It is an evergreen tree native to the Amazon region. According to traditional uses, it is used as a diaphoretic, narcotic, purgative, among other uses. Objective: To evaluate the antioxidant capacity, quantify phenols and total flavonoids of extracts obtained from Ilex guayusa leaves. Methods: Total ethanolic extract was obtained using Soxhlet-type equipment, with subsequent liquid/liquid fractionation with solvents of different polarities (petroleum ether, dichloromethane, and ethyl acetate); were reacted with 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS•+), determining the inhibitory concentration 50 (IC50) and relative antioxidant activity (%AAR), with subsequent statistical analysis (ANOVA and Tukey's post-hoc). Total phenols and flavonoids were quantified using the Folin-Ciocalteu method and complex formation with AlCl3, respectively. Results: The ethanolic extract of leaves showed the highest antioxidant activity in both the DPPH• and ABTS•+ methods with IC50 values of 4.58 and 3.82 ppm, respectively. Conclusions: According to the results obtained in this study, it was possible to corroborate that the ethanolic extract (EE) obtained from the leaves of I. guayusa showed the highest antioxidant capacity, by the DPPH• and ABTS•+ methods. Additionally, it was possible to relate this capacity to the high flavonoids content present in this extract. Based on the above and accompanied by future studies, the Ilex guayusa species could be proposed as an important source of antioxidant compounds with possible application in medicine and the food industry.